How to Misuse Drugs - I.R. Edwards (AOSIS, 1978)
Most of us, during our training, are taught about the actions of drugs and their side-effects, but very few of us are taught how to misuse drugs. However, this is an art that seems to be acquired through practice in handling drugs, by various members of the medical and nursing professions, as well as by the general population. The purpose of this paper is to demonstrate a few of the ways in which drugs can be, and are, misused.